2015
DOI: 10.1002/bit.25554
|View full text |Cite
|
Sign up to set email alerts
|

Protein deimmunization via structure‐based design enables efficient epitope deletion at high mutational loads

Abstract: Anti-drug immune responses are a unique risk factor for biotherapeutics, and undesired immunogenicity can alter pharmacokinetics, compromise drug efficacy, and in some cases even threaten patient safety. To fully capitalize on the promise of biotherapeutics, more efficient and generally applicable protein deimmunization tools are needed. Mutagenic deletion of a protein’s T cell epitopes is one powerful strategy to engineer immunotolerance, but deimmunizing mutations must maintain protein structure and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…The Lib10 variants manifested a loss of 3-9.5°C in thermostability, with the six-and seven-mutation variants having greater reductions than the four-and five-mutation variants. Importantly, however, the melting temperatures (T m ) of the selected Lib10 variants were generally similar to those of fourto eight-mutation P99βL variants deimmunized in earlier studies (18)(19)(20). Thus, rigorous kinetic and thermostability analysis of the selected Lib10 variants, combined with the MHC II-binding assays described above, demonstrated that the library design algorithms achieved both objectives, reducing immunoreactivity and maintaining stability and activity.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The Lib10 variants manifested a loss of 3-9.5°C in thermostability, with the six-and seven-mutation variants having greater reductions than the four-and five-mutation variants. Importantly, however, the melting temperatures (T m ) of the selected Lib10 variants were generally similar to those of fourto eight-mutation P99βL variants deimmunized in earlier studies (18)(19)(20). Thus, rigorous kinetic and thermostability analysis of the selected Lib10 variants, combined with the MHC II-binding assays described above, demonstrated that the library design algorithms achieved both objectives, reducing immunoreactivity and maintaining stability and activity.…”
Section: Resultssupporting
confidence: 52%
“…Such high mutational loads may be important for achieving deimmunization against genetically diverse patient populations or when seeking to deimmunize proteins replete with immunogenic epitopes. In prior studies, smaller numbers of P99βL T-cell epitopes had been deleted by the introduction of two to eight mutations (3,(18)(19)(20)32). Here, deimmunized P99βL libraries produced highly active variants bearing as many as 16 mutations, and in several cases the engineered enzymes possessed equivalent stability and higher catalytic activity than the parental P99βL protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis uses a list of 15 reference alleles and treats each of them with equal importance following a prediction strategy that is considered to be state of the art (Iwai et al, 2003; Tangri et al, 2005; Koren et al, 2007; Cantor et al, 2011; Abdel-Hady et al, 2014; King et al, 2014; Li et al, 2014; Salvat et al, 2014; Salvat et al, 2015); however, it may introduce a bias because those alleles actually have different frequencies in the population. For example, if a peptide is predicted positive to DRB1*0701 (which is the most frequent in the world population), but negative to DRB1*0401 (which is much less frequent in the world population (Gonzalez-Galarza et al, 2011)), those predictions are considered equally important in the in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous restriction assays we have done for epitope 1 (peptide 15) using 10 donors that had a positive response to that epitope showed that this epitope is restricted by DR alone (Mazor et al, 2012). Moreover, focus on DR binding prediction is considered highly common in the art of immunogenicity prediction (Iwai et al, 2003; Tangri et al, 2005; Koren et al, 2007; Cantor et al, 2011; Abdel-Hady et al, 2014; King et al, 2014; Li et al, 2014; Salvat et al, 2014; Salvat et al, 2015) and it has been recently shown that prediction of DP and DQ had very low correlation with experimental data. (Paul et al, 2015) Therefore, we chose to focus only on DR.…”
Section: Discussionmentioning
confidence: 99%